Cotton-hydrogel composite for improved wound healing: Antimicrobial activity and anti-inflammatory evaluation—Part 2 - Pinho, Eva (2018)
Infection is one of the major risk factors for the development of chronic wounds. Antimicrobial wound dressing has been pointed out as a viable option for the prevention and treatment of wound infections. Thus, we developed a composite material based on cotton textile substrates functionalized with cyclodextrin‐hydroxypropyl methyl cellulose‐based hydrogel. The composites' ability to encapsulate and release gallic acid (antimicrobial phenolic acid) was evaluated, as well as their mechanical properties and antimicrobial and anti‐inflammatory capacity. All composites were able to retain gallic acid in their structure, with similar loading profile. The presence of gallic acid on composites was confirmed by FTIR and TGA. Composites storage moduli was reduced by the presence of gallic acid. The results suggest a straight relation between the swelling ability and gallic acid drug delivery profile. The drug delivery mechanism, of the developed composites, was mainly controlled by Fickian diffusion, based on the experimental data fitting to the Peppas‐Sahlin model. Gallic acid antimicrobial and anti‐inflammatory properties were transferred to the composite materials. According to the results, the developed composites can be applied on the prevention or treatment of chronic wounds.